Hearing loss in inherited peripheral neuropathies: Molecular diagnosis by NGS in a French series. Issue 9 (8th August 2019) - Lerat, Justine; Magdelaine, Corinne; Roux, Anne‐Françoise; Darnaud, Léa; Beauvais‐Dzugan, Hélène; Naud, Steven; Richard, Laurence; Derouault, Paco; Ghorab, Karima; Magy, Laurent; Vallat, Jean‐Michel; Cintas, Pascal; et al.
Abstract: Background: The most common inherited peripheral neuropathy is Charcot‐Marie‐Tooth disease (CMT), with a prevalence of 1/2500. Other symptoms can be associated to the condition, such as hearing loss. Currently, no global hearing impairment assessment has been determined, and the physiopathology is not well known. Methods: The aim of the study was to analyze among a French series of 3, 412 patients with inherited peripheral neuropathy (IPN), the ones who also suffer from hearing loss, to establish phenotype‐genotype correlations. An NGS strategy for IPN one side and nonsyndromic hearing loss (NSHL) on the other side, were performed. Results: Hearing loss (HL) was present in only 44 patients (1.30%). The clinical data of 27 patients were usable. Demyelinating neuropathy was diagnosed in 15 cases and axonal neuropathy in 12 cases. HL varied from mild to profound. Five cases of auditory neuropathy were noticed. Diagnosis was made for 60% of these patients. Seven novel pathogenic variants were discovered in five different genes: PRPS1; MPZ ; SH3TC2 ; NEFL; and ABHD12 . Two patients with PMP22 variant, had also an additional variant in COCH and MYH14 respectively. No pathogenic variant was found at the DFNB1 locus. Genotype‐phenotype correlations do exist, especially with SH3TC2, PRPS1, ABHD12, NEFL, a nd TRPV4. Conclusion: Involvement of PMP22 is not enough to explain hearing loss in patients suffering from IPN. HL can be due to cochlear impairment and/or auditory nerve dysfunction. HL is certainly underdiagnosed, and should be evaluated in every patient suffering from IPN. Abstract : The aim of the study was to analyze among a French series of 3, 412 patients with inherited peripheral neuropathy (PN), the ones who also suffer from hearing loss, to establish phenotype‐genotype correlations. An NGS strategy for PN one side and nonsyndromic hearing loss (NSHL) on the other side, were performed.